G207 Is There a Link Between ADHD and Social Deprivation?. (4th June 2013) - Apperley, L; Mittal, R
Abstract : Aim: Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder that affects approximately 4–6% of school-aged children. Research into the aetiology of ADHD has focussed on genetic and biological factors, with much less information on environment and social aspects. There is a general perception that ADHD is linked to deprivation, but there are not enough studies in literature to prove or disprove this assumption. The aim of this study was to investigate the relationship between social deprivation and ADHD. Method: We included all patients diagnosed with ADHD by the community paediatric department (only those on medications). Postcodes of these patients were used to produce deprivation scores, which included overall deprivation and sub-scores for income, social and housing factors. Indices of Deprivation 2010 are available for 32, 482 small geographical areas (Lower Super Output Areas, LSOAs) in England, ranked from 1 (most deprived) to 32, 482 (least deprived). These are further divided into fifths to produce English deprivation quintiles. Each postcode was then allocated to a quintile based on their deprivation score, where quintile 1 represents the most deprived. Results: A total of 144 patients diagnosed with ADHD were being treated with medication. The male to female ratio was 4.5:1 (M: F). The deprivation scores were calculated and it showed that 64 patients (44.4%) were in the most deprived quintile (quintile 1), and followed in a relatively linear pattern. A similar pattern was seen for income, crime, employment, education, skills and training domain and health deprivation and disability, where 69, 57, 74, 69 and 59 patients were placed in quintile 1, respectively. Conclusion: Our study shows an association between the prevalence of ADHD in children and deprivation index. Also there is clear link between sub scores for income, crime, employment, education, skills and training domain and health deprivation and disability and prevalence of ADHD. Indices of deprivation could be used to predict the expected prevalence of ADHD within the community and thus plan allocation of resources. Ours is a small sample size, but results support further investigation with a larger study.